On Hyponormal Toeplitz Operators with Trigonometric Polynomial Symbols - Phukon, Ambeswar (Communications in Mathematics and Applications, 2015)
This paper gives a necessary and sufficient conditions for the hyponormality of a Toeplitz operator \(T_φ\) on the trigonometric polynomial symbol of the type \(φ(z)=\sum_{n=-N}^Na_nz^n\) under some certain assumptions of the Fourier coefficients of \(φ\).